An unfinished life John F. Kennedy, 1917-1963 - Dallek, Robert (Back Bay Books/Little Brown and Company, 2003)
Chronicles John F. Kennedy's childhood, wartime actions, political campaigns, presidency, marriage and personal life, and health, revealing insights into his life from new documents, archives, and firsthand sources